2004
DOI: 10.1007/s00330-003-2146-7
|View full text |Cite
|
Sign up to set email alerts
|

MR mammography in the pre-operative staging of breast cancer in patients with dense breast tissue: comparison with mammography and ultrasound

Abstract: The aim of this study was to determine whether pre-operative MR mammography could predict the extent of breast cancer in patients with dense breasts or whether dense parenchyma will lead to false-positive or inconclusive examinations. Sixty-seven patients with dense breasts with a malignant breast tumor planned for conservative surgery were reviewed. Detection rates of mammography, ultrasound, and MR mammography were studied, and the diameters of the lesions were measured and compared with pathological examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 36 publications
3
80
0
3
Order By: Relevance
“…In particular, DBC proved an extremely highly sensitive diagnostic method in the detection of cancer in patient with ipsilateral multifocal/multicentric carcinomas, either invasive or in situ, and in those with synchronous bilateral tumours, resulting positive in 93.2% of cases. As reported in literature, conventional mammography detected multifocality/ multicentricity in only the 47.5% on cases, demonstrating lower performance than DBC which identified a significantly higher number of additional invasive tumour foci (89.6% vs. 37.9%), most clinically occult and small in size [11,12]. The preoperative underestimation of local disease can lead to surgical under-treatment, resulting in a higher risk of local and distant recurrence.…”
Section: Conventional Nuclear Imaging Breast Scintigraphymentioning
confidence: 69%
“…In particular, DBC proved an extremely highly sensitive diagnostic method in the detection of cancer in patient with ipsilateral multifocal/multicentric carcinomas, either invasive or in situ, and in those with synchronous bilateral tumours, resulting positive in 93.2% of cases. As reported in literature, conventional mammography detected multifocality/ multicentricity in only the 47.5% on cases, demonstrating lower performance than DBC which identified a significantly higher number of additional invasive tumour foci (89.6% vs. 37.9%), most clinically occult and small in size [11,12]. The preoperative underestimation of local disease can lead to surgical under-treatment, resulting in a higher risk of local and distant recurrence.…”
Section: Conventional Nuclear Imaging Breast Scintigraphymentioning
confidence: 69%
“…Similar data was presented by Ando and colleagues, 17 who demonstrated a good correlation between direct invasion of mammary tissue, satellite nodule formation and intraductal tumour extension with histopathology. In the study by Van Goethem, 7 mentioned previously, the comparative sensitivity of MRI was 98% and tumour size was only underestimated by 12.5%. The detection rate for multicentric disease was 100%, although the false-positive rate was elevated, with respect to XRM and USS, at 23%.…”
Section: Magnetic Resonance Imaging: Review Of Literaturementioning
confidence: 78%
“…7 The clinical effectiveness and costeffectiveness of routine dental checks: a systematic review and economic evaluation.…”
Section: Q8 Satisfaction With Shape Of Breastmentioning
confidence: 99%
“…Studies have shown that the sensitivity of MRI for breast cancer detection range from 91% -100%. [158][159][160][161] Supplemental MRI has been shown to improve diagnostic yield by 18.2% per 1000 women. 159 Importantly, MRI is very accurate in excluding the risk of tumour recurrence, with enhancement indicating risk of tumour recurrence and vice-versa.…”
Section: Imaging the Dense Breastmentioning
confidence: 99%
“…[162][163][164] MRI has been shown to be the most accurate imaging modality for examination of the dense breast. 161 Therefore breast density assessment is important for radiographers and radiologists advise women with dense breasts of the most suitable imaging modality and screening interval so that cancer is detected early. 165 …”
Section: Imaging the Dense Breastmentioning
confidence: 99%